2022
DOI: 10.3389/fgene.2021.787767
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Arsenic-Related Traits, Including Rice Grain Arsenic Concentration and Straighthead Resistance, as Revealed by Genome-Wide Association

Abstract: There is global concern that rice grains and foods can contain harmful amounts of arsenic (As), motivating breeders to produce cultivars that restrict As accumulation in grains to protect human health. Arsenic is also toxic to plants, with straighthead disorder (StHD), causing panicle sterility, being observed in rice. The genetic variation in StHD resistance suggests that plants have evolved mechanisms that reduce As toxicity, possibly via regulation of As uptake, transport, or detoxification/sequestration. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 117 publications
2
12
0
Order By: Relevance
“…A total of 4 out of the 14 MTAs, on chromosomes 3, 4 and 5, namely qSSi3.2, qSSi4.2, qSSi5.1, qSSi5.2, respectively, were simultaneously found to be signi cant in 5 out of the 6 ML-GWAS models. Six MTAs identi ed in our study have been found to be co-localized with QTLs from other mapping studies for silica content(Dai et al 2005;Wu et al 2006;Pinson et al 2022), thus providing analytical corroboration to our current study (Table2). Trait Associations (MTAs)/Single Nucleotide Polymorphisms (SNPs) associated with straw silica content in O. nivara accessions, along with previously reported QTLs for Silica, Arsenic (As) and Germanium (Ge)…”
supporting
confidence: 90%
See 4 more Smart Citations
“…A total of 4 out of the 14 MTAs, on chromosomes 3, 4 and 5, namely qSSi3.2, qSSi4.2, qSSi5.1, qSSi5.2, respectively, were simultaneously found to be signi cant in 5 out of the 6 ML-GWAS models. Six MTAs identi ed in our study have been found to be co-localized with QTLs from other mapping studies for silica content(Dai et al 2005;Wu et al 2006;Pinson et al 2022), thus providing analytical corroboration to our current study (Table2). Trait Associations (MTAs)/Single Nucleotide Polymorphisms (SNPs) associated with straw silica content in O. nivara accessions, along with previously reported QTLs for Silica, Arsenic (As) and Germanium (Ge)…”
supporting
confidence: 90%
“…Further, our study found three QTLs to be co-localizing with previously reported QTLs for As content. qSSi4.2 was found to be co-localized with qAs4, while qSSi11.1 and qSSi11.2 co-localized with qAs11-2 identi ed by Pinson et al (2022). In addition, qSSi11.1 was found to be co-localized with qGAs18 and qGAs22 identi ed by Liu et al…”
Section: Straw Silica Content Variationmentioning
confidence: 71%
See 3 more Smart Citations